Influence of component content of Ar/O₂ mixture on oxygen dissociation degree in plasma of low pressure discharge with hollow cathode - Bazhenov, V.Yu.; Lavrookevich, Yu.V.; Piun, V.M.; Ryabtsev, A.V.; Tsiolko, V.V. (Вопросы атомной науки и техники, 2015)
Influence of argon content in Ar/O₂ mixture on O₂ dissociation degree and atomic oxygen concentration in the plasma of low pressure glow discharge with hollow cathode is determined experimentally and theoretically. It is found that atomic oxygen concentration dependence on argon content in the mixture exhibits non-monotonous behavior with a minimum at Ar/(Ar+O₂) ≈ 50%. Results of calculation and experiment are in a good agreement.